La Russia nella prima e seconda globalizzazione. Differenze e similarità - Caselli, Gian Paolo (European Journal of Sustainable Development, 2014)
<!--[if gte mso 9]> <![endif]--> The recent process of globalization is transforming the world economy into one big market. All barriers to economic homogenization represented by the existence of barriers of trade and by the movement of factors of production are being overwhelmed by the joint force of technical progress, and by the growing importance of finance in the current economic decisions. The dynamics of globalization can not be determined, anyway we can have important lessons from the past, for a better understainding of the present world. This study examines the current process of globalization in relation with the Russian economy, comparing it with the previous period of globalization. Most of the economists in the world, consider that there are two periods of globalization: the first one being from 1870-80 to 1914 and the second from 1980 to the present day, whose effects unfolding around the globe, we currently experience. Russia at that period, like all countries of the world, has had to adapt to the process of globalization, facing that reality and struggling to find a role in the international division of labor. This article aims to demonstrate that the two periods for Russia have deep common features, but also many big differences. Key Words: Russia, Globalization, Economic Development, Industrial Policy <!--[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->